(3Gdbhd GdhLjR aj CMcGe GdcJGH GdYRjRs - (3CMeO Hf jhSa Hf YHO GdOGje GdMdHj, CHh GdYHGS, TgGH GdOjf GdeYQha HGdSejf,J (B756 (3g` s
(3BNQgG (B:s
(3hgh GYdi deMd GdfRGY dGSde Gf GdYeQ cGf YGQi Ydi edc GdePchQ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B211s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1366s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJaSjQ hYdhe GdbQBfs